2022
DOI: 10.1038/s41598-021-04299-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of suction blister epidermal grafting and automated blister epidermal micrograft in stable vitiligo

Abstract: The automated blister epidermal micrograft (ABEM) is a newly introduced surgical transplantation for refractory vitiligo. Comparative analysis of other surgical methods is lacking. We conducted a retrospective study to compare the efficacy, safety, and experience of ABEM with conventional suction blister epidermal graft (SBEG). A total of 118 anatomically based vitiligo lesions from 75 patients were included. The primary outcome was the degree of repigmentation; the patient and operator experience were evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…These results were consistent with previous studies. 5,6 Postoperative AEs at the recipient site, such as erythema, pain, and itching, generally resolved within 1 month without requiring treatment. It was noted that 74.7% (189/253) of patients experienced perigraft halo and 46.2% (117/253) had persistent halo, which was slightly higher than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These results were consistent with previous studies. 5,6 Postoperative AEs at the recipient site, such as erythema, pain, and itching, generally resolved within 1 month without requiring treatment. It was noted that 74.7% (189/253) of patients experienced perigraft halo and 46.2% (117/253) had persistent halo, which was slightly higher than those reported in the literature.…”
Section: Discussionmentioning
confidence: 99%
“…The main AE in the donor site was cobblestone-like pigmentation in 73.1% (185/253) of cases, and in 28.9% (73/253) of patients, the pigmentation persisted for more than 2 years without regression. In 2022, Gao et al 6 used the traditional negative pressure blistering method to extract 62 blisters and observed their AEs, and they observed that the cobblestone-like pigmentation in the blister area took an average of approximately 13.71 months to regress. The authors concluded that cobblestone-like pigmentation in the donor site is a common AE of SBEG, and it takes a long time to regress.…”
Section: Discussionmentioning
confidence: 99%
“…According to the nature of the grafts, it can be divided into tissue grafting and cellular grafting ( 22 ). Tissue grafting, such as suction blister grafting, costs about 100 CNY per square centimetre in China, and is simple to perform, but it is generally suitable for small areas and skin lesions in specific areas ( 23 ). In addition, progress has been made in cellular grafting in recent years.…”
Section: Discussionmentioning
confidence: 99%
“…Although ABEM is expensive, it is relatively convenient and provides a larger transplanting area. In a comparative study involving 75 patients, SBEG had better re-pigmentation than ABEM, while ABEM allowed for improved treatment satisfaction with a better operative experience ( 36 ).…”
Section: Surgical Interventionmentioning
confidence: 99%